178k views
0 votes
If f(x) = 3x - 2 and g(x) = 2x + 1, find (f - g)(x)

User SNM
by
6.0k points

2 Answers

7 votes

Answer:

( f - g ) ( x ) = x - 3

Explanation:

We are to find
( f - g ) ( x ) given that
f ( x ) = 3 x - 2 and
g ( x ) = 2 x + 1.

So basically we have to subtract the function g from function f.


( f - g ) ( x ) = f(x) - g(x)

Substituting the given functions in the above equation to get:


( f - g ) ( x ) = (3x - 2) - (2 x + 1 )


( f - g ) ( x ) = 3x - 2 - 2 x - 1


( f - g ) ( x ) = 3x - 2 x - 2 - 1


( f - g ) ( x ) = x - 3

User Jamesmoschou
by
5.3k points
5 votes

Answer:

(f-g)(x) = x-3

Explanation:

Given

f(x) = 3x-2

and

g(x) = 2x+1

We have to find (f-g)(x)

So,

(f-g)(x) = f(x)-g(x)

= 3x-2 - (2x+1)

= 3x-2-2x-1

=x-3

Hence,

(f-g)(x) = x-3

User Jon Cram
by
6.4k points